Effects of Hindlimb Suspension on the Development of Hip Bone Morphologies in Growing Rats - Ezumi, S; Kaneguchi, A; Kanehara, M; Iwamoto, Y; Takahashi, M; Nishida, N; Ozawa, J (Physiological research, 2024)
Abnormal hip bone morphologies are associated with various diseases of the hip joint. Weight bearing, especially during growth, may be important to achieve normal acetabulum development. This study aimed to investigate whether hip bone morphologies were affected by hindlimb suspension (HS) in 4 week-old rats. In HS groups, tail suspension was applied for 0, 2, 4, and 8 weeks. Age-matched rats were used as controls. The complex of hip bones with lumbar and sacral vertebrae were assessed based on morphological indexes using three-dimensional reconstructed images from X-ray computed tomography. Acetabular widths (measured from cranial to caudal) unchanged and depths became larger in both groups with age. Acetabular lengths (from the ventral side to the dorsal side) became larger in control groups but unchanged in HS groups with age. In HS groups, acetabular width, length, and depths were smaller than the control groups at 4 and/or 8 weeks. Acetabular versions became enlarged (rotated inwards) with age in both groups, although this was particularly pronounced in HS groups. Histologically, triradiate cartilage layers in the acetabulum were thinner with age and almost disappeared at 8 weeks in both groups. However, HS decreased Safranin O staining and prolonged the presence of hypertrophic chondrocyte indicating alterations in the chondral ossification processes. Iliac wing angles remained unchanged and anterior superior iliac crest (ASIC) distances increased with age in controls. In contrast, HS groups showed narrowed iliac wing angles with small ASIC distances. These results suggest that reduced mechanical loading during growth can interfere with hip joint formation. Keywords Hindlimb suspension, Hip joint, Acetabular morphology, Triradiate cartilage.
Keywords: zadní končetina - imobilizace; krysa rodu Rattus; Animals; acetabulum; Rats, Sprague-Dawley; Acetabulum; Hindlimb Suspension; mužské pohlaví; zvířata; Male; potkani Sprague-Dawley; Rats